Holistic Medicine in Health Communication Approach - Dwi Andriani, Astri (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
This research is quoted to see the phenomenon of holistic treatment based on a health communication approach. To get this result, this research uses a descriptive qualitative approach where by collecting data that is supplied by sentences in it. Literature Review Steps include: Systematic Identification, Document Analysis containing information about the problem of problems. In this study, data collection methods used by researchers are documentation methods, data on data about matters or variables in books, newspapers, journals, and so on. Books, literature, and notes about the problems to be discussed. The techniques used are content analysis or content review. The results of this study are: Holistic treatment is a comprehensive treatment that the model uses a biomedical approach and complementary and alternative drugs. In the implementation of holistic medicine, communication activities between medical officers and patients use the principles of therapeutic communication. One important principle in therapeutic communication is a service that is centered. Holistic Treatment Supporting Model is a treatment model that is centered on Planetree Patients (PPCC) is very suitable for boarding in holistic treatment.